From Pearl Harbor to the Paris Attacks: Political-Military Surprises and the Conditions that Cause Them - Moretti, Rebecca (Colloquium: The Political Science Journal of Boston College, 2017)
Although in hindsight the element of surprise in attacks often appears unwarranted, various conditions inherent to intelligence organizations, policy makers, and adversaries make this evidence difficult to spot before the fact. In this essay, I demonstrate how cognitive biases, the nature of the adversary, and bureaucratic deficiencies are all conditions that facilitate surprises. Finally, I conclude that surprise is inevitable in some cases.